Morphological changes in the iliac artery walls of pigs after implantation of spiral devices from β-zirconium alloy - Zakharova, V. P.; Panichkin, Yu. V.; Skiba, I. O.; Zhuravleva, M. L.; Beshlyaga, V. M.; Beshlyaga, E. V.; Ruzhin, Yu. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The results of histological studies of the iliac arteries of pigs wall after the implantation of the spiral device – occluder, made on the basis of low modulus β-zirconium alloy. It is shown that in 2.5 months after the introduction into the lumen of the artery of the occluder, a capsule is formed around of neointimal fibrosis, which overlaps occluder more than 2/3 of the lumen of the vessel, indicating a good device occlusive effect.